Spatiotemporal analysis of oil palm land clearing - M.K. Rosyidy; E. Frimawaty (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Oil palm is one of the crops that has an essential role in Indonesia's engineering field. This condition has led to oil palm plantation intensification, which has been extensive to deforestation in Indonesia, including Jambi province. The main aim of this investigation is to evaluate deforestation and land change affected by oil palm expansion conducted by smallholders, which influences environmental change using remote sensing combined with a geographic information system approach. This study utilizes the change of oil Palm in spatial-temporal (spatial and temporal) in Jambi province related to land change and environmental impacts.METHODS: This research uses data from Landsat 8 satellite imagery. The land cover classification was done using the Maximum Likelihood approach, while the overlay method was used for land change analysis. Accuracy assessment of classification results uses a confusion matrix taking into account overall accuracy and Kappa Hat. Within the field observation, the validation class is the oil palm class, using documentation and plotting using the global positioning system, and other classes are validated using the Region of Interest collected through Google Earth. This research uses Aviation Reconnaissance Coverage Geographic Information System 10.1 software to transform the categorization results into vector data. FINDINGS: This study shows that the landcover classification results have high accuracy. This study shows that the area of oil palm land from 2015 to 2019 has increased along with a decrease in land used, such as forests and others. The area of oil palm land 2014 was 2,071,345 hectares, while the area in 2019 was 2,110,545 hectares. In other words, there was an increase in land cover due to land clearing and deforestation, namely 39.2 thousand hectares. The built-up area has also increased in the last five years, namely 165,358 hectares. The number of oil palm plantations tends to be greater in relatively plain areas compared to areas with relatively high altitudes and steep slopes. Small farmers'''' area of oil palm land increased by 1,000 hectares in 2014-2018. The most significant increase occurred in 2016-2017, around 38,889 hectares.CONCLUSION: This study demonstrates that using Landsat 8 imagery combined with GIS approaches provides the optimal method for an in-depth analysis of land cover changes related to oil palm expansion and land clearing that occur on a broader spatial scale and temporal in Jambi Province. This study shows that smallholder oil palm plantations in the Jambi region play an important role in increasing deforestation in Jambi Province, especially in Indonesia. This study is expected to serve as a valuable resource for informing policy decisions aimed at addressing the issue of deforestation resulting from the prospective increase of oil palm crops in the forthcoming period.